Design and optimization of cascade organic Rankine cycle for recovering cryogenic energy from liquefied natural gas using binary working fluid. (August 2015) - Kim, Kyeongsu; Lee, Ung; Kim, Changsoo; Han, Chonghun
Abstract: A cascade power generation system that utilized the cold exergy of liquefied natural gas (LNG) was proposed in this study. The proposed system adopts binary working fluids for each stage to minimize the exergy destroyed in the condensers of each stage of the cycle. The best combination of working fluids was selected through minimization of the amount of destroyed exergy by varying the flow rate, composition, and pressure of the working fluid. After selecting the working fluids, process optimization was performed through a parametric study. In addition, a sensitivity analysis was performed to observe the effect of temperature variation of the heat sources in the range of 25–85 °C on the net power generation. As a result, the proposed cycle generated 151.78 kJ/h kgLNG under a 25 °C heat source and showed an efficiency of 18.64%. The performance of the proposed cycle was linearly increased according to the temperature of heat source. For instance, the proposed system generated 248.79 kJ/h kgLNG, with exergy efficiency of 27.11% under an 85 °C heat source. Highlights: Binary mixture working fluid cascade ORC utilizing LNG cold energy is proposed. Optimum working fluid and process configuration are obtained via an optimization. The power generation of the ORC can reach 157.76 kJ/kgLNG under 25 °C heat source. A sensitivity analysis for heat source in the range of 25–85 °C was performed.